DIFFERENCES IN THE DISTRIBUTION OF INHERITANCE ISLAMIC LAW AND BATAK LECTURES - Herlina Hanum Harahap; Indra Fauzi; Supian Supian (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2023)
Customary inheritance is the process by which tangible and intangible property is inherited and passed on from generation to generation. The customary law of inheritance contains provisions on the transfer of property and intangible property from generation to generation to their descendants. An heir is a person who dies, whether male or female, leaving behind a portion of the property acquired and the rights and obligations that must be exercised during his lifetime, whether by will or not. The legal basis for the crown prince to bequeath part of the crown prince's property according to BW inheritance law. Many or at least the share that the heirs receive from the applicable law. Therefore, all heirs have the same inheritance. Meanwhile, batak customary punishment is based on the provisions of the law and ordinary presidential orders on the division of inheritance.